Attitudes of Israeli parents of children with Down syndrome toward non‐invasive prenatal screening and the scope of prenatal testing. Issue 6 (30th August 2019) - Nov‐Klaiman, Tamar; Raz, Aviad E.; Hashiloni‐Dolev, Yael
Abstract: Due to its early utilization and increasing ability to provide genetic information, non‐invasive prenatal screening (NIPS) has reinforced social and bioethical quandaries concerning prenatal genetics. This paper presents exploratory findings based on 20 semi‐structured interviews conducted in 2017–2019 with Israeli parents of children with Down syndrome (DS), four of whom also serving as representatives of DS organizations. Their views are presented regarding the pros and cons of NIPS; the social context of decision‐making about NIPS; and views on life with DS and termination of pregnancies on that ground. While illustrating the large heterogeneity of views concerning NIPS and prenatal diagnosis (PND) amongst parents of children with DS, our respondents commonly criticized the imbalanced information provided by professionals regarding DS, seen as sending a discriminating message in line with the public ignorance surrounding DS. These views are further discussed in the multi‐cultural, ableist and pro‐natal context of Israeli society. We conclude by offering practical implications concerning NIPS, parental autonomy, and informed choice.